2014
DOI: 10.1111/desc.12242
|View full text |Cite
|
Sign up to set email alerts
|

Call me Alix, not Elix: vowels are more important than consonants in own‐name recognition at 5 months

Abstract: Consonants and vowels differ acoustically and articulatorily, but also functionally: Consonants are more relevant for lexical processing, and vowels for prosodic/syntactic processing. These functional biases could be powerful bootstrapping mechanisms for learning language, but their developmental origin remains unclear. The relative importance of consonants and vowels at the onset of lexical acquisition was assessed in French-learning 5-month-olds by testing sensitivity to minimal phonetic changes in their own… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
120
7
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(137 citation statements)
references
References 50 publications
9
120
7
1
Order By: Relevance
“…Indeed, months before their first birthday, infants show modest but consistent comprehension for common and proper nouns that are frequent in their daily input (Bergelson & Swingley, 2012, 2015; Bouchon, Floccia, Fux, Adda-Decker, & Nazzi, 2015; Parise & Csibra, 2012; Tincoff & Jusczyk, 1999, 2012). In the subsequent months, comprehension improves, and production begins (Fenson, Dale, Reznick, & Bates, 1994; Fernald, Pinto, Swingley, Weinberg, & McRoberts, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, months before their first birthday, infants show modest but consistent comprehension for common and proper nouns that are frequent in their daily input (Bergelson & Swingley, 2012, 2015; Bouchon, Floccia, Fux, Adda-Decker, & Nazzi, 2015; Parise & Csibra, 2012; Tincoff & Jusczyk, 1999, 2012). In the subsequent months, comprehension improves, and production begins (Fenson, Dale, Reznick, & Bates, 1994; Fernald, Pinto, Swingley, Weinberg, & McRoberts, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Bouchon et al. () showed that French‐learning 5‐month‐olds could detect a vowel change in their own name and not a consonant change, but also that infants reacted to the acoustic distance between vowels. Here, we tested British English‐learning 5‐month‐olds in a similar study to examine whether the acoustic/phonological characteristics of the native language shape the nature of the acoustic/phonetic cues that infants pay attention to.…”
mentioning
confidence: 99%
“…In the present study, we embarked on an extension of Bouchon et al. 's study () to British English, for a number of reasons. First, English and French are contrasted on a number of acoustic and phonological parameters that could impact differently task complexity when infants are presented with minimally different stimuli (Pater, Stager, & Werker, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent work suggests that vowels are more important than consonants in lexical recognition for infants: When 5-month-olds are presented with mispronunciation of the onset of their own name, which either began with a vowel or a consonant, infants' looking patterns suggested that own-name recognition is disrupted to a greater extent by the vowel change than the consonant change [21]. Thus, at least at young ages, vowels seem a reasonable choice for assessing potential phonology-lexicon interactions.…”
Section: Discussionmentioning
confidence: 99%